Momentopname. - Gierstberg, Frits; Van Caldenborgh, J.N.A. (Rotterdam : Caldic Collectie, 1996)
Kertesz, André ; Feininger, Andreas ; Koppitz, Rudolf ; Muybridge, Eadweard ; Curtis, Edward S. ; Man Ray ; Besnyö, Eva ; Zoetmulder, Steef ; Finkelstein, Nat ; Rauschenberg, Robert ; Hockney, David ; Doisneau, Robert ; Jaar, Alfredo ; Wall, Jeff ; Prince, Richard ; Sherman, Cindy ; Becher, Bernd & Hilla ; van Lamsweerde, Inez ; Strand, Paul ; Lange, Dorothea ; Weegee ; Karsh, Yousuf ; Newman, Arnold ; Horst, Horst P. ; Dahl-Wolfe, Louise ; Matiz, Leo ; Chochola, Vaclav ; Elenbaas, Esther ; van Os, Pim ; Blumenfeld, Erwin ; Elenbaas, Wally ; Greene, Milton ; Schatt, Roy ; Zimbel, George ; Halsman, Philippe ; Karsh, Yousuf ; Webb, Todd ; Bernhard, Ruth ; Arbus, Diane ; Friedlander, Lee ; Broodthaers, Marcel ; Schwarzkogler, Rudolf ; Gibson, Ralph ; Graham, Dan ; Paolini, Giulio ; Mapplethorpe, Robert ; Erwitt, Elliott ; Salgado, Sebastião ; Baldessari, John ; Kounellis, Jannis ; Ruff, Thomas ; Michals, Duane ; Becher, Bernd & Hilla ; Förg, Gunther ; Knoebel, Imi ; Kenna, Michael ; de Jong, Anja ; Gursky, Andreas ; Struth, Thomas ; Huf, Paul ; Close, Chuck ; Majore, Frank ; Wegman, William ; Sturges, Jock ; Mann, Sally ; Henson, Bill ; Weber, Bruce ; Cravo-Neto, Mario ; Geleynse, Wyn ; Lemieux, Annette ; Casaer, Paul ; Boltanski, Christian ; Messager, Annette ; Levine, Sherrie ; Simmons, Laurie ; Prince, Richard ; Longo, Robert ; Kaap, Gerald Van Der ; Scholte, Rob ; Tan, Fiona ; van Golden, Daan ; McDermott & McGough ; Serrano, Andres ; Simpson, Lorna ; Ulay ; Jaar, Alfredo ; Barney, Tina ; Wall, Jeff ; Lafontaine, Marie-Jo ; Finke, Romy ; Dunning, Jeanne ; Lamers, Ine ; Mik, Aernout ; Manders, Mark ; Wilschut, Hans ; Koelewijn, Job ; Loodwicks Press Images ; Charlesworth, Sarah ; Smit, Pépé ; Noordenbos, Corinne ; Koop, Wanda ; Post, Liza May ; etc.
Momentopname, Caldic Collectie, Rotterdam, 1996
Nederlands
boek